ANALYSIS OF THE RELATIONSHIP BETWEEN PARENTAL INVOLVEMENT AND STUDENT ACHIEVEMENT IN INCLUSIVE EDUCATION - Anggreni; Niswa Hasanah; Mardiana (Adisam Publisher, 2025)
This research analyzes the relationship between parental involvement and student achievement in the context of inclusive education. Through a comprehensive literature review, this research aims to explore how active parental participation influences student learning outcomes, especially for those with special educational needs. Various previous studies show that parental involvement plays a key role in supporting student motivation, engagement, and academic achievement. More specifically, emotional and academic support from parents has been proven to strengthen children's self-confidence and enthusiasm for learning. In addition, collaboration between parents, teachers and school institutions is considered very important to create a learning environment that is inclusive and responsive to individual student needs. This research also highlights the importance of partnerships between families and communities in providing additional resources and ongoing support programs. Results from this literature indicate that parental involvement not only has an immediate positive impact on student achievement, but also builds a strong foundation for long-term success in the context of inclusive education. It is hoped that these findings can become a reference for further educational practitioners, policy makers and researchers in developing effective strategies that support parent participation and improve inclusive student educational outcomes.